INCREASING LEARNING MOTIVATION AND LEARNING OUTCOMES IN MATHEMATICS USING MODULES FOR ELEMENTARY SCHOOL STUDENTS - triyanto, aan titik; Aryani, Ine Kusuma (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
Abstract. This study aims to look at the use of modules to improve learning motivation and learning outcomes in mathematics for elementary schools. Modules are a source of learning in learning activities. Modules can be either manual or e-modules. The type of data used is secondary data. The method used in this research is the literature study method. The data obtained were compiled, analyzed, and concluded in  to get conclusions about the literature study. Based on the research results of literature studies from several research results and books and journal articles, it shows that: (1) the use of modules can increase student motivation. (2) the use of modules can improve student learning outcomes.